Estructuración del proyecto para la implementación de una escuela de canes en la ciudad de Quito - Méndez Simbaña, Carmen Elizabeth (2009)
The proposed implementation of a Escuala for dogs is created with the aim of providing an attractive alternative to the market, households that after the acquisition of a dog face a number of problems (disobedience), thus offering a possible solution to problem getting obedience through education.